Evaluasi Pelaksanan Sertifikasi Guru Sekolah Umum dan Guru Sekolah Madrasah - Budi Budi (Badan Strategi Kebijakan Hukum, 2012)
Teacher certification is a government policy that has a noble purpose to improve the quality of education and welfare of teachers, considering the magnitude services of a teacher in educating generation of people. Teacher certification is aimed to improving the quality of education and welfare of teachers. The purpose of this study is to analyze the concept, implementation and impact of teacher certification, and to formulate a reorientation of the conception and implementation of teacher certification. The method used is a qualitative approach, which falls into the category of policy analysis, on the basis of review and synthesis on the processed data and related information.Such goodwill has unfortunately been tainted by the fact that there has been a swift of paradigm among teachers. Initially, their main purpose to be a teacher is to transform science and to educate students to become better than before. But now, such a noble intention has been changed to a merely certificates oriented.